Literature Review: KOL Marketing sebagai Strategi Pemasaran Digital di Era Sosial 5.0 - Lailiyah, Nita Ilmiyatul (SAFE-Network, 2023)
The Social Era 5.0 presents significant changes in the marketing strategies used by companies in interacting with consumers. In this era, the role of Key Opinion Leaders (KOL) is becoming increasingly important in influencing consumer behavior and achieving company marketing objectives. Companies should focus on using digital platforms, social media and other new technologies to reach their target audience. The role of KOL is also very important in the Social Era 5.0 marketing strategy. KOL has great influence on digital platforms and can influence consumer preferences. Through their endorsements, product reviews and recommendations, KOL can help companies expand market reach and build consumer trust. Companies need to forge strong partnerships with KOLs relevant to their industry to achieve optimal marketing results. The Social 5.0 era requires companies to adopt marketing strategies that suit current technological characteristics and trends. By leveraging the latest digital and technology platforms, and forging strong partnerships with KOL, companies can achieve marketing success in this Social 5.0 Era. The data collection methods used in this research include identifying, evaluating, interpreting and searching for literature from various reliable sources such as reviewing journals related to the methods used both accredited local, national and international journals. The articles referred to in this study totaled 21 journal articles published from 2018-2022. Researchers collected the 20 articles from several journal search websites such as; google scholar, Crossref, and IEEE with the keywords Key Opinion Leader, Digital Marketing Strategy, and Social Era 5.0.